2002
DOI: 10.1006/nimg.2001.1001
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study of Bilingual Sentence Comprehension and Workload

Abstract: To examine the relation between the cortical substrates that support the comprehension of one's native language and those that support a second language, fMRI measures of cortical activation were taken as native Japanese participants, who had acquired moderate fluency in English, listened to auditory sentences in Japanese and English. In addition, to examine the impact of processing difficulty within a language, sentence difficulty was manipulated by including affirmative (easy) and negative (hard) sentences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
7
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(167 citation statements)
references
References 40 publications
11
146
7
3
Order By: Relevance
“…Neuroimaging studies suggest that foreign language comprehension requires more cognitive resources than native language comprehension (Hasegawa, Carpenter, & Just, 2002), perhaps because foreign language users "must devote more cognitive resources to lower level processes, such as word identification, semantic access, and syntactic processing" (Miller & Keenan, 2011, p. 874). Critically, studies suggest that cognitive depletion prompts a reduced consideration of intentions versus outcomes in moral evaluations (e.g., Buon, Jacop, Loissel, & Dupoux, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies suggest that foreign language comprehension requires more cognitive resources than native language comprehension (Hasegawa, Carpenter, & Just, 2002), perhaps because foreign language users "must devote more cognitive resources to lower level processes, such as word identification, semantic access, and syntactic processing" (Miller & Keenan, 2011, p. 874). Critically, studies suggest that cognitive depletion prompts a reduced consideration of intentions versus outcomes in moral evaluations (e.g., Buon, Jacop, Loissel, & Dupoux, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that some of the empirical evidence for neural dissociation for late-acquisition bilinguals might have been confounded by language proficiency (Perani et al, 1998), time of exposure , or task difficulty (Chee et al, 2001). To disentangle these confounding factors (especially task difficulty), the effect of workload needs to be taken into consideration (Hasegawa et al, 2002), a point to which we will return in the next section.…”
Section: Neural Dissociation and Overlap Between L1 And L2 In Wmmentioning
confidence: 99%
“…On the one hand, research has shown that brain lesion causes equal deficit of working memory capacity in bilinguals' two languages, which suggests common or largely overlapping neural networks for WM processing in L1 and L2 (van Lieshout et al, 1990;Warren et al, 2000). In addition, several functional imaging studies of bilinguals have found common activation for the two languages in the abovementioned three components of the working memory system: the executive system (Hernandez et al, 2000(Hernandez et al, , 2001, the speech/rehearsal system (Hasegawa et al, 2002;Kim et al, 1997;Klein, 2003;Klein et al, 1995Klein et al, , 1999Rodriguez-Fornells et al, 2002), and the retention/storage system (Hasegawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations